Biofunctionalization of conductive hydrogel coatings to support olfactory ensheathing cells at implantable electrode interfaces. Issue 4 (6th August 2015) - Hassarati, Rachelle T.; Marcal, Helder; John, L.; Foster, R.; Green, Rylie A.
Abstract: Mechanical discrepancies between conventional platinum (Pt) electrodes and neural tissue often result in scar tissue encapsulation of implanted neural recording and stimulating devices. Olfactory ensheathing cells (OECs) are a supportive glial cell in the olfactory nervous system which can transition through glial scar tissue while supporting the outgrowth of neural processes. It has been proposed that this function can be used to reconnect implanted electrodes with the target neural pathways. Conductive hydrogel (CH) electrode coatings have been proposed as a substrate for supporting OEC survival and proliferation at the device interface. To determine an ideal CH to support OECs, this study explored eight CH variants, with differing biochemical composition, in comparison to a conventional Pt electrodes. All CH variants were based on a biosynthetic hydrogel, consisting of poly(vinyl alcohol) and heparin, through which the conductive polymer (CP) poly(3, 4‐ethylenedioxythiophene) was electropolymerized. The biochemical composition was varied through incorporation of gelatin and sericin, which were expected to provide cell adherence functionality, supporting attachment, and cell spreading. Combinations of these biomolecules varied from 1 to 3 wt %. The physical, electrical, and biological impact of these molecules on electrode performance was assessed. Cyclic voltammetry and electrochemical impedance spectroscopy demonstrated that the addition of these biological molecules had little significant effect on the coating's ability to safely transfer charge. Cell attachment studies, however, determined that the incorporation of 1 wt % gelatin in the hydrogel was sufficient to significantly increase the attachment of OECs compared to the nonfunctionalized CH. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 104B: 712–722, 2016.